Late Wisconsinan And Holocene Sedimentation Of Silverhope Valley, British Columbia - Goff, James Rodney (Scholarship@Western, 1993)
Sixty-eight bedrock and sediment exposures, six lake bottom cores, and twenty-six bulk samples of river gravels were studied by various stratigraphic methods including: radiocarbon and caesium dating, tephrochronology and lithofacies analysis to interpret late Wisconsinan and Holocene deposits in the Silverhope Creek drainage basin.;Late Wisconsinan evidence suggests that during the downwasting and retreat of the Cordilleran Ice Sheet between approximately 11 500 and 11 000 years BP, there was one minor readvance and two smaller standstill/oscillations. During deglaciation a dead ice-dammed lake formed in front of the retreating ice mass. Partial lake drainage occurred initially by catastrophic flooding through dead ice into the contiguous Chilliwack valley over a low pass. Subsequent lake levels were controlled by dead ice decay, hummocky terrain, ice marginal drainage and height of the retreating ice mass. Final drainage occurred as a small outburst into the Fraser valley. Tributary glaciers appear to have retreated at different rates and to be, at times, temporarily covered by water.;Burial of Mazama tephra found in paraglacial alluvial fans suggests that following deglaciation, meltwater reworking of glacial sediments was more rapid on the west side of the drainage basin.;Landslide-damming (probably not seismic-generated) of Silver Lake appears to have taken place around 1100 A.D. Radiocarbon ages indicate that sedimentation in the lake occurred at a rate of about 0.14 cm adollar\sp{lcub}-1{rcub}{dollar} until 1946, with Silverhope Creek forming a delta into the southwest side of the lake. In 1946, diverted flows built a new delta into the southeast side of Silver Lake at the commencement of major logging activity and road construction around and to the south of Silver Lake. Caesium-137 traces indicate that post-1946 sedimentation rates have increased to approximately 2.75 cm adollar\sp{lcub}-1{rcub}.{dollar} Rates do not appear to have declined significantly in the last twenty to thirty years.;Analysis ...